2002
DOI: 10.2307/3060978
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Plan Revisions: Progress or Due Process?

Abstract: Revisions allow the recovery planning process for threatened and endangered species to be flexible and responsive to new information or changes in the status of a species. However, the Endangered Species Act defines neither firm criteria that trigger revision of recovery plans nor clear guidelines about how plans should be revised. Consequently, the effect of revisions in the recovery planning process is unknown. We examined how species and recovery plan attributes influenced the likelihood that a plan would b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…These preliminary plans could consist largely of research protocols to investigate threat factors. Plans would then be given priority for revision when new information becomes available (see also Harvey et al 2002). Implementation of multi-species recovery plans will only be simpler and more cost effective if species are grouped into plans, or management units within larger plans, to efficiently mitigate or eliminate common threats.…”
Section: Discussionmentioning
confidence: 99%
“…These preliminary plans could consist largely of research protocols to investigate threat factors. Plans would then be given priority for revision when new information becomes available (see also Harvey et al 2002). Implementation of multi-species recovery plans will only be simpler and more cost effective if species are grouped into plans, or management units within larger plans, to efficiently mitigate or eliminate common threats.…”
Section: Discussionmentioning
confidence: 99%
“…Funding for recovery plans is limited, but it is imperative to determine the factors that lead to recovery of listed populations and to maximize efforts to remove species from the list (Lawler et al, 2002). Data on species-habitat interactions as habitat associations, spatial variation in habitat quality, and dietary requirements should be included in recovery plans to augment more efficient recovery (Harvey et al, 2002;Moore and Gillingham, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…But our knowledge of species and threats-consider the emergence of our understanding of climate change in the past decades-can change rapidly. A previous analysis found that revisions did not improve recovery criteria (Harvey, Hoekstra, O'Connor, & Fagan, 2002), but we anticipate that recovery will be more successful if plans contain up-to-date information beyond original recovery criteria.…”
Section: How Old Are Recovery Plans As Of 2018?mentioning
confidence: 72%